Diterpenoids with inhibitory activity of nitrite production from Croton floribundus - Queiroz, Suzana Aparecida S. [UNESP] (2020)
Ethnopharmacological relevance: Croton floribundus Spreng. (Euphorbiaceae), popularly known as Capixingui, stands out due to its widespread use in traditional medicine to treat wounds, syphilis, hemorrhoids, eye diseases and as a purgative. Aim of the study: To characterize clerodanes diterpenes from C. floribundus and to evaluate the effects of the fraction and diterpenes (1-5) on inhibition of nitrite production. Materials and methods: The hydroethanolic root extract of C. floribundus was fractionated on a solid phase extraction column to obtain the fraction named Fr80%. From this, five compounds were obtained and characterized. The absolute configuration of compound 1 was determined by a combination of electronic and vibrational circular dichroism spectroscopies. Additionally, compounds 1-5 were evaluated for their inhibitory effects on nitrite production induced by lipopolysaccharide (LPS) in RAW 264 macrophage cell. Results: Five clerodane diterpenoids were characterized, and the absolute stereochemistry of 1 was established as 3R,4R,5R,8R,9R,10S,12S. The IC50 values obtained through inhibition of nitrite production were 28.52 +/- 2.21 mu M (1), 40.26 +/- 2.79 mu M (2), 25.47 +/- 2.16 mu M (3), 35.78 +/- 2.93 mu M (4) and 40.58 +/- 4.78 mu M (5). In the tested concentrations, the samples presented low toxicity in macrophages. Conclusions: Four new diterpenes were characterized from C. floribundus, these being croflorins A-D (1-4) and a known halimane (5). These compounds exhibited inhibitory effect on nitrite production.